2003
DOI: 10.1152/ajpgi.00109.2003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antral contractions and vagal afferent signaling with synchronized electrical stimulation

Abstract: Gastric filling activates vagal afferents involved in peripheral signaling to the central nervous system (CNS) for food intake. It is not known whether these afferents linearly encode increasing contractions of the antrum during antral distension (AD). The aim of this study was to investigate effects of AD and electrically enhanced antral contractions on responses of vagal afferents innervating the antrum. Single-fiber recordings were made from the vagal afferents in anesthetized male Long-Evans rats. Antral c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 36 publications
(48 reference statements)
1
52
0
1
Order By: Relevance
“…In another rodent study, vagal afferent fibres were activated when antral contractions were induced with GES. 59 …”
Section: Involvement Of Vagal Afferent Pathwaymentioning
confidence: 99%
“…In another rodent study, vagal afferent fibres were activated when antral contractions were induced with GES. 59 …”
Section: Involvement Of Vagal Afferent Pathwaymentioning
confidence: 99%
“…Using an advanced spectral analysis of heart rate variability for the assessment of vagal activity, GES is found to be involved with increased vagal activity and accelerated gastric emptying in dogs and rats (Liu et al 2004;Ouyang et al 2003). Additionally, GES is reported to produce an increase in the firing rate of vagal single afferent fibers associated with antral contractions of the stomach in rats (Peles et al 2003), and GES mainly exerts excitatory effects on NTS neuronal activity (Qin et al 2005). However, some investigators noted a role of sympathetic pathways in the effects of GES on gastrointestinal functions.…”
Section: Afferent Pathwaysmentioning
confidence: 99%
“…Previous studies using atropine and vagotomy in dogs have indicated that vagal afferent and/or efferent pathways are involved in the regulation of GES on gastric motility Grundfest-Bronaltowski et al 1990;Liu et al 2004;Ouyang et al 2003). In rats, GES can activate vagal afferent fibers innervating the stomach (Peles et al 2003) and modulate neuronal activity in the nucleus tractus solitarii, where vagal afferent fibers terminate (Qin et al 2005). A few recent studies suggest that the effects of GES with different parameters on gastric motility also involve the sympathetic nerve system.…”
Section: Introductionmentioning
confidence: 99%
“…For example, GES increases the firing rate of single vagal gastric afferent fibers and mainly exerts excitatory effects on neuronal activity in the nucleus tractus solitarii in rats (Peles et al 2003, Qin et al 2005. Vagotomy eliminates the anti-emetic effects of short-pulse GES on nausea and vomiting induced by vasopressin .…”
Section: Afferent Pathwaysmentioning
confidence: 99%
“…Effects of GES on gastric motility have been shown to involve vagal afferent and/or efferent pathways in dogs Grundfest-Bronaltowski et al 1990;Liu et al 2004;Ouyang et al 2003). In rats, GES can activate vagal afferent fibers innervating the stomach (Peles et al 2003) and modulate activity of neurons in the nucleus tractus solitarii receiving gastric vagal afferents (Qin et al 2005). A few recent studies further suggest that effects of GES with varying parameters on gastric motility involve the sympathetic alpha-and beta-adrenergic sympathetic efferent pathways system (Zhu and Chen 2005;Ouyang et al 2005).…”
Section: Introductionmentioning
confidence: 99%